Refined numerical modelling for the structural assessment of steel-concrete composite beam-to-column joints under seismic loads - Amadio, Claudio; Bedon, Chiara; Fasan, Marco; Pecce, Maria Rosa (Engineering structures, 2017)
•A welded steel-concrete composite joint designed in accordance with the Eurocode 4 is extensively investigated.•Refined full 3D solid FE numerical simulations are presented joint and critically discussed.•FE validation and assessment is carried out in terms of global and local (component) behaviour.•Rather close agreement with the test results is found, including local phenomena.•Based on the FE predictions, possible review of the actual Eurocode design provisions is suggested. This paper proposes a refined Finite-Element (FE) numerical approach to predict both global and local behaviour of steel-concrete composite welded joints subjected to seismic loads. The reference FE model is implemented in ABAQUS and first extensively validated to the full-scale experimental results of a welded steel-concrete composite specimen tested in a past research project, where the beam-to-column sub-assemblages were designed according to the prescriptions of Eurocode 4 and Eurocode 8. As shown, due to the FE modelling assumptions, a rather close agreement was generally found between the FE predictions and the corresponding test measurements, both in terms of global and local phenomena. Therefore, it is first expected that such numerical approach could be implemented as an alternative to costly and time consuming full-scale experimental tests, allowing an extensive parametric investigation of composite joints and possible design optimizations. An implicit advantage of the implemented FE model, in fact, is that according to a refined analysis of the experimental and numerical results for the welded joint object of investigation, the efficiency of the Eurocode 8 design prescriptions for steel-concrete composite joint details can be critically discussed and reviewed. In the specific case, a possible improvement of the design recommendations for the slab reinforcement around the column is proposed.